2012
DOI: 10.1002/psc.2439
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and properties of cyclic gomesin and analogues

Abstract: Gomesin (Gm) was the first antimicrobial peptide (AMP) isolated from the hemocytes of a spider, the Brazilian mygalomorph Acanthoscurria gomesiana. We have been studying the properties of this interesting AMP, which also displays anticancer, antimalarial, anticryptococcal and anti-Leishmania activities. In the present study, the total syntheses of backbone-cyclized analogues of Gm (two disulfide bonds), [Cys(Acm)(2,15)]-Gm (one disulfide bond) and [Thr(2,6,11,15),(D)-Pro(9)]-Gm (no disulfide bonds) were accomp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 56 publications
1
17
0
3
Order By: Relevance
“…Alternatively, loss of their activity may involve partial hydrolysis of the N-terminal N 7 -amide to α- or β-monocarboxylic acid residues (X-Asn-OH or X-Asp-NH 2 ) via an aminosuccinimide intermediate [22]. Therefore we performed plasma stability studies for both NM4A and NM4-C 16 analogs using full length hNmU as a comparator [6769]. Results (Figure 5C) indicated that both analogs have significant resistance to mouse plasma driven enzymatic degradation, with NM4-C 16 being more stable than NM4A.…”
Section: Resultsmentioning
confidence: 99%
“…Alternatively, loss of their activity may involve partial hydrolysis of the N-terminal N 7 -amide to α- or β-monocarboxylic acid residues (X-Asn-OH or X-Asp-NH 2 ) via an aminosuccinimide intermediate [22]. Therefore we performed plasma stability studies for both NM4A and NM4-C 16 analogs using full length hNmU as a comparator [6769]. Results (Figure 5C) indicated that both analogs have significant resistance to mouse plasma driven enzymatic degradation, with NM4-C 16 being more stable than NM4A.…”
Section: Resultsmentioning
confidence: 99%
“…Relatos na literatura indicam maior resistência à proteólise do AMP com a amidação da sua porção C-terminal 34 ou ciclização envolvendo aminoácidos D e L. 53 Em relação ao alto custo de produção, estudos da relação estrutura-atividade vem sendo realizados com o objetivo de gerar peptídeos menores, portanto, mais baratos, tão ou mais ativos do que os naturais. 53 Quanto à redução de potência em alta força iônica, pesquisas indicam que mudanças na hidrofobicidade, anfipaticidade, carga e grau de a-hélice auxiliam a solucionar o problema. 53 Assim, pode-se comparar os AMPs e os antimicrobianos disponíveis no mercado (Tabela 2).…”
Section: Potencialidades E Dificuldades De Uso De Amps Na Terapêuticaunclassified
“…53 Quanto à redução de potência em alta força iônica, pesquisas indicam que mudanças na hidrofobicidade, anfipaticidade, carga e grau de a-hélice auxiliam a solucionar o problema. 53 Assim, pode-se comparar os AMPs e os antimicrobianos disponíveis no mercado (Tabela 2).…”
Section: Potencialidades E Dificuldades De Uso De Amps Na Terapêuticaunclassified
“…Examples of such structures are cyclic depsipeptides, 2 glutathione, the conotoxins, 3 and the trypsin inhibitor SFTI-1, with a single disulfide bridge. 4 The biological and medical significance of cyclic peptides as potential therapeutics is evinced by an increasing number of publications describing their antiviral, 5 hemolytic 6 and anti-helminthic 7 activities. Cyclic peptides owe at least a part of their importance in nature to their tendency to resist degradation by exopeptidases.…”
Section: Introductionmentioning
confidence: 99%